PENERAPAN TERAPI DZIKIR MEDITASI PADA LANSIA YANG MENGALAMI STRESS - Rosmin Ilham; Hamna Vonny Lasanuddin; Miranti Abdullah (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Introduction: Elderly is a life where from babies, toddlers, teenagers, adults and the elderly. In this process there are significant Bio-Psycho-Social changes in his life such as social changes, namely the breaking of relationships with colleagues, loss of status or role (tasks, authorities and responsibilities) in the workplace environment, changes in individual roles in the family and public. Method: The research method used in this study is a qualitative descriptive research method. The collection techniques for this research were interviews, observations, physical examinations and documentation. Results: The results showed that before giving dhikr and meditation therapy, 4 patients (80%) were in the moderate stress category, and 1 patient (20%) was in the severe stress category. After giving dhikr and meditation therapy, 4 patients (80%) were found with mild stress category, and 1 patient (20%) with moderate stress category. Conclusion: Prior to the remembrance therapy, the mental condition of the elderly at the Peni Griya Jannati experienced depression due to the pressures of daily life, experiencing loneliness due to living with family or loved ones, mental emotional disorders that were not yet stable, and anxiety disorders. So that the process of dhikr therapy must be carried out in the elderly.